ANALISIS VEGETASI POHON DI HUTAN HUJAN TROPIK HARAPAN, JAMBI - Muhammad Mansur; Teguh Triono; Ismail Ismail; Setyawan Warsono Adi; Enu Wahyu; Gofar Ismail (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Vegetation analysis of trees in Harapan Rainforest, PT.REKI, Jambi, was conducted on October-November 2009. Two 50m x 100m (0,5 ha) plots were established to obtain primary data for analysis. Plot one was made in the area of Medium Secondary Forest and plot two in the area of High Secondary Forest. Results shows that, the number of tree species were recorded from the two plots was 205 species from 550 individual trees with a total Basal Area (BA)= 64.75 m2. Plot one has 123 species from 284 individuals with BA = 10.82 m2 and Diversity Index (H')= -1.87. Bellucia axinanthera was recorded as the dominant species with Importance Value (IV)= 37.21%. Meanwhile, plot two has 126 species from 266 individuals with BA= 53.93 m2 and (H')= -1.97. Shorea acuminata was recorded as the dominant species with IV= 12.93%. Plot two (High Secunder Forest) has higher diversity of tree species than plot one (Medium Secunder Forest).The structure and composition of vegetation between plot one and plot two is different with similarity index for the two plots is only 21.46%.